Thorpe–Ingold Effect on High-Performance Chiral π–Copper(II) Catalyst - Nishimura, Kazuki; Ishihara, Kazuaki (Synlett, 2022)
The Thorpe–Ingold effect was applied to the design of a chiral ligand of π–copper(II) catalysts for the enantioselective α-fluorination of N-acyl-3,5-dimethylpyrazoles, and also for the enantioselective Mukaiyama–Michael, Diels–Alder, and 1,3-dipolar cycloaddition reactions of N-acryloyl-3,5-dimethylpyrazoles. The use of β,β-dimethyl-β-arylalanine-type ligand gave desired products with higher enantioselectivity compared to with previously reported β-arylalanine-type ligands.
Keywords: π–copper(II) catalyst; chiral catalyst; Lewis acid; enantioselective; Diels–Alder reaction; Mukaiyama–Michael reaction; 1,3-dipolar cycloaddition; α-fluorination